Diseño de un modelo de planeación de inventarios en una empresa distribuidora de GLP (Gas licuado del petróleo) que permita un adecuado control - Pabón Ceballos, Leidy Dadiana; Castañeda Quiroz, Jhon Jader (Universidad Antonio Nariño, 2022)
The present research work arises from the need to improve the current inventory model of the Liquefied Petroleum Gas - LPG distribution company, in it there is an inefficiency in said management for the consumption of its products; This has caused an accumulation of low-rotation products and shortages in high-rotation products, therefore, when analyzing the behavior of demand and cylinders per item, it was possible to identify the main problems in the inventory area, which allowed determining a adequate forecast simulation model for each item, analyzing the pattern presented by its demand, where the processes were optimized by reducing the times in it, all this under a statistical analysis approach developed by the researchers